PENGARUH BIAYA PEMASARAN TERHADAP HASIL PENJUALAN FOLDING GATE DAN ROLLING DOOR MFG PADA PT PUTRA AGUNG SANTOSO - Bowo Lestono (Jurnal Ekonomi dan Manajemen, 2018)
Background in this research is the production as well as in marketing experience of increase or decrease, but nevertheless company can’t know for sure whether sales volume of Folding Gate and Rolling Door Mfg at PT. Son Agung Santoso in Samarinda is as a positive result of marketing expenditure activities performed or not. The formulation of the problem in this research is: "Is There Positive Influence of Marketing Cost of Sales Volume Folding Gate and Rolling Door Mfg at PT. Son of the Great Santoso in Samarinda? This study aims to determine the magnitude of the effect of marketing costs on sales volume Folding Gate and Rolling Door Mfg made by PT. Son of the Great Santoso in Samarinda. Based on the result of calculation of analysis and discussion, hence obtained result that marketing cost have influence very weak or small to sales volume of Folding Gate And Rolling Door Mfg at PT. Son of Agung Santoso in Samarinda for year 2014 can be seen in regression equation that is: Y = 285.945,033 + 215,720X, meaning every increase of marketing cost equal to Rp 215,720,00 which will lead to increase to sales volume of Folding Gate And Rolling Door Mfg at PT. Son Agung Santoso in Samarinda Rp 285,945,033.00 The amount of correlation coefficient (r) is 0.3602 or 0.36%, also has been proven by t test count greater than t table (1.2210> 1.1392). While the year 2015 with regression equation that is: Y = 210.904,044 + 172,279 (X), meaning every increase of marketing cost equal to Rp 172.279,00 will cause increase to sales volume of Folding Gate and Rolling Door Mfg at PT. Son of Agung Santoso in Samarinda Rp 210.904.044,00. The magnitude of correlation coefficient (r) is 0.7500 or 0.75%, with t count is greater than t table (3.5857> 2.7652), this means that the year 2015 tesrsebut between variable X marketing costs have a very positive or very strong with variable Y sales volume Folding Gate and Rolling Door Mfg on PT. Son of the Great Santoso in Samarinda, thus, the hypothesis which the authors point out is true and acceptable.